Performance analysis of a proposed geothermal pile system for heating and cooling energy demand for a building in cold regions. (February 2019) - Saaly, Maryam; Maghoul, Pooneh; Kavgic, Miroslava; Polyzois, Dimos
Highlights: Re-harvest of the heat leaked through the buildings below grade envelope into the ground in urban areas can favorably impact the geothermal energy piles functionality. If the mitigation methods can be applied for meeting the thermal balance of the ground, geothermal energy piles can be well suited in urban areas. Length of the piles and the operational strategy of the them can significantly affect the thermal balance of the ground and further efficiency of the geothermal energy piles. Solar water heater unit (SWHT) can efficiently be used as an auxiliary system which aids meeting the thermal balance of the soil. Abstract: In this paper, the performance of a proposed geothermal energy pile system for the energy demand of an institutional building is investigated. The building studied in this research is situated in the Fort-Garry campus of the University of Manitoba in the southernmost portion of Winnipeg (MB) in Canada. In an urban area, underground temperatures are substantially higher than the surrounding rural areas due to the buildings heat leakage to their underneath ground. In this study, this heat loss is harvested through geothermal piles and rejected to the building for the HVAC system utilization. The underground thermal imbalance, which is the most common problem encountered while utilizing the geothermal energy in cold regions, is extensively studied. It is concluded that despite the heat leakage through the basement enclosure, thermal balance of the soil, in case of supporting the total energy demand of the building by geothermal piles, cannot be met. The application of some auxiliary heat sources is proposed. Finally, the amount of energy harvested from the ground is calculated by maintaining the thermal balance of the soil and preventing the freezing at the soil-pile interface which affects adversely the structural performance of geothermal piles.